Transmissão, detecção e controle de didymella bryoniae em pepino e infecção em melão - Moura, Gabriela Silva (2013)
The culture of cucumber (Cucumis sativus L.) and melon belongs (Cucumis melo L.) belong the Cucurbitaceaes family. This family consists of about 80 genera and more than 800 species, constituting one of the most important families of plants used for food production worldwide. In southern Paraná, has been a major focus for the cultivation of parthenocarpic cucumber and muskmelon, performed under conditions of protected cultivation, especially in plastic greenhouses. In southern Paraná, has been given great emphasis on the cultivation of parthenocarpic cucumber, conducted under greenhouse conditions, basically in plastic greenhouses. In this agroecosystem, fungal pathogens, such as the causal agent of gummy rot (Didymella bryoniae) can cause damage to various magnitudes, including agribusiness derail when control strategies are inadequate. Symptoms and damage can vary depending on the age of the plant and the affected part. In seedlings, the pathogen can cause tipping, as well as circular spots on the cotyledons. In more developed plants, causes cancer stems with longitudinal splitting of the wood cortex and exposure sometimes with exudate gum, which results in the death of the whole plant or branch, depending on the injury site. In leaves, necrotic spots appear circular that grow and coalesce, causing partial burning. In fruits, dark spots can occur, circulars and in-depth, with exudation of gum. Roots of cucumber, when infected, have dark color due to the presence pseudothecium. The control of decay gummy can be done through use of pathogen free seeds, crop rotation, elimination of wild cucurbits, disinfestation of the soil cultivation, use of fungicides and adequate irrigation. Currently there is no reports of cucumber germplasm resistant to D. bryoniae. Thus the forms used for the control of D. bryoniae have been the seed treatment and fungicide sprays registered for culture. For parthenocarpic cucumber, few studies have been developed addressing on this pathosystem in the world, and especially in Brazil. Thus, this study investigated the transmission of D. bryoniae seed to plant and rot control in cucumber gummy Japanese in muskmelon. In Chapter I, for testing transmission in a green house the percentage of transmission of D. bryoniae was 7.0% and 11.5% for the commercial substrate base carborizada bark of Pinus sp. soil and sand, respectively. In the tests where the incubation chamber, the transmission was 3.5% and 1.5% water-agar substrate and vermiculite, respectively. The transmission of the pathogen D. bryoniae on cucumber seeds was vi experimentally demonstrated by test symptoms in seedlings in vitro and in vivo, with greater incidence when transplanted to substrate: sand. In Chapter II, it was possible the qualitative detection of the pathogen D. bryoniae, by Multiplex PCR, the three quantities used cucumber seeds (50, 100 and 200) without soaking in water. In Chapter III, from the Multiplex PCR, we determined the presence of the pathogen in asymptomatic plants, demonstrating the occurrence of latent infection in parthenocarpic cucumber seedlings. In Chapter IV, the results showed that seed treatment combination for foliar culture with pyraclostrobin are efficient strategy for the control of brown rot in Japanese cucumber hybrid gummy ?Hokushin? grown in greenhouse. In the summer-autumn crop was obtained higher productivity parthenocarpic cucumber over the spring-summer cultivation. In Chapter V, the results showed an effect of grafting in reducing injuries to rot in cucumber gummy parthenocarpic ?Hokushin?. For plants inoculated in the hypocotyl graft and inoculated in the region graft / rootstock, injuries hit area of 3,45 and 2,57 cm2, respectively. In Chapter VI, by Multiplex PCR, we determined the stem of asymptomatic plants of melon noble the occurrence of latent infection. In asymptomatic stem fragments at 5, 15 and 30 cm tissue symptomatic melon noble was possible to prove the systemic infection of D. bryoniae.